2011
DOI: 10.1021/bc200397j
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide–Polyethylenimine Nanoconstruct as a Gene Delivery Vector and Bioimaging Tool

Abstract: Graphene oxide (GO) has attracted an increasing amount of interest because of its potential applications in biomedical fields such as biological imaging, molecular imaging, drug/gene delivery, and cancer therapy. Moreover, GO could be fabricated by modifying its functional groups to impart specific functional or structural attributes. This study demonstrated the development of a GO-based efficient gene delivery carrier through installation of polyethylenimine, a cationic polymer, which has been widely used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
284
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(286 citation statements)
references
References 42 publications
2
284
0
Order By: Relevance
“…In addition, the positive charges of PEI facilitate the release of the cargo from the endosome thanks to the "proton sponge" effect. The most common approach consists of the covalent engraftment of polyethylanimine (PEI) via EDC/ NHS chemistry onto both GO and reduced GO (rGO) flakes 34,[37][38][39][40][41][42][43][44][45][46][47] . Noncovalent but electrostatic interactions have also been used to anchor PEI onto graphene nanoribbons (GNR) 48 , GO 49 and rGO/Au composites 50 .…”
Section: Strategies To Optimize Gbms As Gene Delivery Platformmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the positive charges of PEI facilitate the release of the cargo from the endosome thanks to the "proton sponge" effect. The most common approach consists of the covalent engraftment of polyethylanimine (PEI) via EDC/ NHS chemistry onto both GO and reduced GO (rGO) flakes 34,[37][38][39][40][41][42][43][44][45][46][47] . Noncovalent but electrostatic interactions have also been used to anchor PEI onto graphene nanoribbons (GNR) 48 , GO 49 and rGO/Au composites 50 .…”
Section: Strategies To Optimize Gbms As Gene Delivery Platformmentioning
confidence: 99%
“…Kim and colleagues not only demonstrated the capacity of covalently linked GO-BPEI to force the expression of a luciferase encoding pDNA in two different cancer cell lines, which was superior to that of BPEI low molecular weight alone and comparable to that of BPEI high molecular weight but with reduced cytotoxicity 38 . The authors also made use of the photoluminescent properties of GO-BPEI, which allowed them to follow the GO-BEPI/pDNA complexes during transfection by confocal microscopy and to confirm that carrier and nucleic acid payload travelled together inside the cells, via complexation with a fluorescently labeled pDNA.…”
Section: Intracellular Molecular Sensingmentioning
confidence: 99%
“…53 Similarly, in another study, Kim et al used PEI functionalized GO sheets for delivering luciferase gene into cells for bioimaging applications. 54 Several other studies utilized this PEI-GO (iii) mRNA Delivery nanoconstruct as a vector and demonstrated highly e±cient delivery of EGFP plasmid DNA into cells in vitro, either in a non-targeted or targeted manner. [55][56][57][58] Recently, the concept of photothermally enhanced gene delivery was introduced for the¯rst time by Feng et al followed by a subsequent study by Kim et al, who independently showed that the transfection e±ciency of graphene-based nanovectors could be improved signi¯cantly by exploiting the NIR responsive photothermal properties of GO and rGO at the time of transfection.…”
Section: Graphene-based Nanomaterials For Nucleic Acid Deliverymentioning
confidence: 99%
“…142 Kim et al synthesized a graphene-based gene delivery vehicle by conjugating low molecular weight branched polyethylenimine (BPEI) to GO sheets, thereby imparting a positive surface charge to the nanoconstruct that ultimately facilitated complexation with negatively charged plasmid DNA through electrostatic interactions and showed e±cient gene delivery to HeLa and PC3 cells in vitro. 54 In addition to this, the authors exploited the intrinsic°uorescence properties of GO for imaging the cellular uptake of the nanoconstructs.…”
Section: Graphene-based Theranostic Platformsmentioning
confidence: 99%
“…Low molecular weight branched polyethylenimine (BPEI) attached GO showed an improved DNA binding, condensation and transfection efficiency compared to high molecular weight BPEI. Due to the tunability of GO, this BPEI@GO hybrid nanocomposite could be extended to SiRNA delivery and PTT [14]. Light controllable CpG-ODNs delivery was proposed and showed excellent photothermal and immunological effects towards the cancer cell tumor reduction in GO@PEG and PEI nanocomposites [15].…”
Section: Drug Delivery and Cancer Therapymentioning
confidence: 99%